1997
DOI: 10.1103/physrevlett.79.5082
|View full text |Cite
|
Sign up to set email alerts
|

Effective Low-Energy Theory for Correlated Carbon Nanotubes

Abstract: The low-energy theory for single-wall carbon nanotubes including Coulomb interactions is derived and analyzed. It describes two fermion chains without interchain hopping but coupled in a specific way by the interaction. The strong-coupling properties are studied by bosonization, and consequences for experiments on single armchair nanotubes are discussed. [S0031-9007(97)04654-1]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
662
4
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(702 citation statements)
references
References 16 publications
33
662
4
3
Order By: Relevance
“…In the case of single nanotubes, the dominant contribution to the forward-scattering couplings in ͑7͒ comes from the strong Coulomb potential in ͑2͒, with some infrared cutoff which is dictated in general by the longitudinal size of the nanotube. 11 This leads to values of the charge stiffnesses that are typically smaller than 1 and in agreement with the experimental observations of Luttinger liquid behavior in the carbon nanotubes. 2,3 For energy scales much lower than E c , however, the rest of the interaction channels neglected in the above analysis may become as important as the forwardscattering channels.…”
Section: ͑15͒supporting
confidence: 71%
See 1 more Smart Citation
“…In the case of single nanotubes, the dominant contribution to the forward-scattering couplings in ͑7͒ comes from the strong Coulomb potential in ͑2͒, with some infrared cutoff which is dictated in general by the longitudinal size of the nanotube. 11 This leads to values of the charge stiffnesses that are typically smaller than 1 and in agreement with the experimental observations of Luttinger liquid behavior in the carbon nanotubes. 2,3 For energy scales much lower than E c , however, the rest of the interaction channels neglected in the above analysis may become as important as the forwardscattering channels.…”
Section: ͑15͒supporting
confidence: 71%
“…9 From a theoretical point of view, it is well-known that the Luttinger liquid regime may break down in the carbon nanotubes, due to a variety of low-temperature instabilities. [10][11][12][13][14][15] When the effective phonon-mediated interactions are taken into account, it can be shown that the superconducting correlations may grow large upon suitable screening of the Coulomb interaction in the nanotubes. 16,17 This has raised the hopes that such correlations could be amplified by considering nanotube geometries with enhanced electron-phonon couplings.…”
Section: Introductionmentioning
confidence: 99%
“…However, carbon nanotubes are known to be described in terms of a four-channel LL 6,7,20 . The four channels are responsible for the charge-flavour (φ c− ), total spin (φ s− ), spin-flavour (φ s+ ) and total charge (φ c+ ) excitations.…”
Section: Field Emission From Luttinger Liquids and Swntsmentioning
confidence: 99%
“…One of the most important of these is the universality class of 1D correlated electrons or the so-called Luttinger liquids (LLs), which are e.g. realised in single-wall carbon nanotubes (SWNTs), as has been shown both theoretically and experimentally 6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…We expect that our results-with the appropriate changes [2] in the equations relating scaling exponents to the LL parameter K-directly carry over to the case of spin-1/2 electrons if the two-particle interaction is long-ranged (unscreened) in real space (that is, if the g 1,⊥ term of the g-ology classification [4] can be neglected) and spin-rotationally invariant. This is generally assumed to be the case in single wall carbon nanotubes [5]. For semiconductor heterostructures the range of the interaction can strongly depend on the ... ... Figure 1.…”
Section: Introductionmentioning
confidence: 99%